Two new species of the lined flat bark beetle genus Laemophloeus Dejean (Coleoptera: Cucujoidea: Laemophloeidae) from Amazonia - Bento, Matheus; Rafael, José Albertino (Zootaxa, 2025)
This paper describes and illustrates two new species of Laemophloeus Dejean (sensu stricto) (Coleoptera: Cucujoidea: Laemophloeidae) from the Amazon region of Brazil: L. claudioruyi sp. nov. and L. obeliscus sp. nov. Both species are diagnosed and compared to their most similar congeners with antennal club composed of 3 antennomeres, primarily based on clypeal, elytral, and genital morphology, allowing for identification. Additionally, the preexisting keys to Laemophloeus species with 3- and 6-segmented antennal clubs are modified and combined into a single key that includes all the Neotropical species of the genus.